Polyester high-strength fiber with high quality and low variable coefficient and application thereof
By controlling the p-methylbenzoic acid content in the polyester slices and using the melt spinning process, high-quality, low-coefficient polyester high-strength fibers were prepared, which solved the existing fiber orientation and spinning stability variability, and achieved the effect of high strength and low coefficient of variation.
Patent Information
- Application Number
- CN202311744143.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-19
- Publication Date
- 2025-03-11
AI Technical Summary
Existing polyester fibers have variability problems in orientation and spinning stability, which is difficult to meet the needs of high strength and low coefficient of variation, especially in areas with high safety requirements such as electric vehicle tires and airbags.
By controlling the content of p-methylbenzoic acid in the polyester slices between 40 and 100 ppm, and the melt spinning process is carried out after alkaline alcoholylation or alkaline hydrolysis, high-quality, low-coefficient polyester high-strength fibers are prepared.
It significantly improves the orientation stability and spinning uniformity of the fibers, increases the elongation of primary fibers, reduces the phenomenon of wool, broken and floating in the spinning process, and meets the needs of high strength and low coefficient of variation.
Smart Images

Figure BDA0004613959940000141 
Figure BDA0004613959940000151 
Figure BDA0004613959940000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high molecular polyester materials, and in particular to a high-strength polyester fiber with high quality and low coefficient of variation and application thereof. Background Art
[0002] With the development of polyester high-strength fiber, in addition to ensuring physical properties, the uniformity and stability of the fiber quality produced is even more important, especially for industrial and automotive related products, which pay special attention to safety performance.
[0003] The orientation of fiber structure refers to the degree of orientation of different structural units of macromolecules or segments in a fixed length of fiber under the action of certain external fields (such as tensile stress or shear stress) along a specific direction. It is an important indicator to characterize the oriented structure of materials. When not oriented, the arrangement of macromolecular chains and segments is random, so they are isotropic. After orientation, since the forces between atoms in the orientation direction are mainly chemical bonds, and in the direction perpendicular to it, the forces between atoms are mainly van der Waals forces, they are anisotropic. Therefore, the mechanical, optical and thermal properties of the material before and after orientation are significantly different. In terms of mechanical properties, to improve the stable tensile strength and flexural fatigue strength, the uniform stability needs to be greatly increased in the orientation direction, while it needs to be reduced in the direction perpendicular to it; in terms of thermal properties, the fiber strength retention rate increases.
[0004] According to the literature "The Effect of PT Acid on the Properties of Polyester and Its Fibers" (Volume 14, Issue 5, 2001, Pages 28 to 30), when synthesizing polyester chips, the monomer purified terephthalic acid (PTA) will contain impurities such as p-toluic acid (PT acid), which will affect the orientation degree and spinning stability of the final polyester fiber. It is concluded that if p-toluic acid (PT acid) exceeds 200ppm, it will have a significant impact on the orientation uniformity, stability and spinning of polyester. The industry controls the p-toluic acid in terephthalic acid, the raw material of polyester chips, at 130-180ppm, which can only meet the minimum requirements of polyester fibers in the Chinese national standard GB / T 16604-2017 Polyester Industrial Yarn Specification. In the face of the increased safety requirements for electric vehicle tires, airbags, safety webbing, industrial fabrics, etc., the requirements for the low coefficient of variation of the physical properties of polyester fibers also need to be improved.
[0005] This application designs a high-quality, low-coefficient-of-variation polyester high-strength fiber and its application, and prepares polyester fibers with high quality and low coefficient of variation by controlling the content of p-toluic acid in polyester chips, which obviously has practical significance. Summary of the invention
[0006] The purpose of the invention is to provide a polyester high-strength fiber with high quality and low coefficient of variation and application thereof.
[0007] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a high-quality and low-variance coefficient polyester high-strength fiber, which is a polyester fiber obtained by processing polyester chips after alkaline alcoholysis or alkaline hydrolysis, and the content of p-toluic acid in the polyester chips after alkaline alcoholysis or alkaline hydrolysis is 40-100 ppm; the processing method includes a melt spinning process.
[0008] Preferably, the melt spinning process includes drying, melt extrusion, melt distribution, component spinning, filament cooling, oiling, drawing and heat setting, and winding of polyester chips having a p-toluic acid content of 40 to 100 ppm obtained by titration test after alkaline alcoholysis or alkaline hydrolysis.
[0009] Preferably, the specific method of the melt spinning process includes the following steps:
[0010] (1) Drying of polyester chips: After drying, the moisture content of polyester chips is controlled to ≤25ppm;
[0011] (2) Melt extrusion, melt distribution, and component spinning: polyester chips with a controlled moisture content of ≤25 ppm are fed into a screw extruder, melted at high temperature, and extruded and fed into component spinning via melt distribution;
[0012] (3) Cooling, oiling, drawing and heat setting of the filaments: The filaments are cooled, oiled and then drawn by hot rollers;
[0013] (4) Winding: The filament bundle is formed into a silk cake through a winding machine, and the winding speed is 2300-6700m / min.
[0014] Preferably, step (1) can be replaced by using polyester low-viscosity chips to continuously increase viscosity and then storing them in a nitrogen or dry air environment with a moisture content of ≤25 ppm.
[0015] Preferably, in step (2), the temperature of each zone in the screw extruder is 276-330° C., the head pressure is 10-17 MPa, the cooling air temperature of the filament bundle is 16-70° C., and the spinneret stretching ratio during the component spinning process is 200-1900.
[0016] Preferably, the oil content of the oil applied in step (3) is between 0.2% and 1.0%, the speed of one roller during hot roller stretching is between 385 and 3650 m / min, the maximum hot roller speed is between 2350 and 6750 m / min, the hot roller temperature during hot stretching is between 45 and 155° C., the hot roller heat setting temperature is between 200 and 260° C.; the total extension ratio is between 1.55 and 6.5; and the retraction speed difference is between 15 and 360 m.
[0017] Preferably, the linear density deviation rate of the polyester fiber is ±2.0%; the strength is ≥6.8 cN / dtex; the coefficient of variation at the breaking elongation is ≤29% is only less than 70% of the upper limit required for superior products in the Chinese national standard GB / T 16604-2017 polyester industrial filament.
[0018] Preferably, the intrinsic viscosity of the polyester fiber is ≥ 0.72 g / dl; more preferably, the intrinsic viscosity of the polyester fiber is ≥ 0.75 g / dl.
[0019] The present application also claims protection for the application of a high-quality, low-coefficient-of-variation polyester high-strength fiber, and the high-quality, low-coefficient-of-variation polyester high-strength fiber described above is applied to tire cord fabric, airbag fabric, car seat belts, conveyor belts, tarpaulins, air spring fabrics, industrial slings, tent fabrics, sewing threads, and dipped cords.
[0020] Preferably, when the polyester high-strength fiber is used in tire cord fabric, its linear density deviation rate is ±1.3%; the breaking strength is ≥7.00cN / dtex, the breaking strength variation coefficient is ≤1.9%, and the breaking elongation variation coefficient is ≤5.5%;
[0021] The spinning process is as follows: the raw materials are input into a screw extruder for high-temperature melting and extrusion into a spinning assembly, the temperature of each zone of the screw is 282-330°C, the head pressure is 11-17 MPa, the temperature of the cooling zone is 17-68°C, the speed of one roller is 2200-3500 m / min, the maximum hot roller speed is 4700-6500 m / min, the heat setting temperature is 210-250°C; the total extension ratio is 1.7-2.5; and the retraction is 60-280 m.
[0022] Preferably, when polyester high-strength fiber is used in industrial slings and automobile seat belts, its linear density deviation rate is ±1.3%; breaking strength is ≥8.2cN / dtex, breaking strength variation coefficient is ≤1.9%, and breaking elongation variation coefficient is ≤5.5%;
[0023] The spinning process is as follows: the raw materials are input into a screw extruder for high-temperature melting and extrusion into a spinning assembly, the temperature of each zone of the screw is 280-315°C, the head pressure is 10-16MPa, the temperature of the cooling zone is 17-27°C, the speed of one roller is 400-1000m / min, the maximum hot roller speed is 2600-4000m / min, the heat setting temperature is 200-258°C; the total extension ratio is 5.4-6.2; and the retraction is 50-280m.
[0024] Preferably, when the polyester high-strength fiber is used for airbag fabric, conveyor belt, tarpaulin, air spring fabric, tent fabric, its linear density deviation rate is ±1.3%; the breaking strength is ≥6.8cN / dtex, the breaking strength variation coefficient is ≤1.9%, and the breaking elongation variation coefficient is ≤5.5%;
[0025] The spinning process is as follows: the raw materials are input into a screw extruder for high-temperature melting and extrusion into a spinning assembly, the temperature of each zone of the screw is 280-315°C, the head pressure is 12-16MPa, the temperature of the cooling zone is 16-25°C, the speed of one roller is 400-1000m / min, the maximum hot roller speed is 2500-3900m / min, the heat setting temperature is 210-260°C; the total extension ratio is 5.1-6.3; the retraction is 80-330m.
[0026] In the above, the method for detecting the content of p-toluic acid in the polyester raw material comprises the following steps:
[0027] S11, cracking the raw material to be tested, decomposing the raw material to be tested into small molecules and producing trace impurities, extracting the small molecules and trace impurities, filtering, washing, and drying to obtain the object to be tested;
[0028] S12, preparing a sample from the test object prepared in step S11, analyzing the sample using a high-efficiency capillary chromatographic column, and testing the impurity content after polyester cracking.
[0029] Preferably, the small molecule comprises PTA (terephthalic acid).
[0030] Preferably, the cleavage in step S11 is carried out by alkaline alcoholysis or alkaline hydrolysis, the cleavage temperature is 120-220° C., and the reaction time is 2-7 hours.
[0031] Preferably, the cracking in step S11 adopts alkaline alcoholysis method, the alcohol used in the alkaline alcoholysis method is methanol or ethylene glycol, and the mass ratio of the raw material to be tested to the alcohol is 1:3-7.
[0032] Preferably, the cleavage in step S11 is performed by alkaline hydrolysis, and the water used in the alkaline hydrolysis is deionized water; the mass ratio of the raw material to be tested to water is 1:3-7.
[0033] Preferably, in step S11, the cracking reaction process further includes adding a catalyst, the catalyst includes sodium carbonate, and the mass ratio of the catalyst to the raw material to be tested is 0.5 to 1:1.
[0034] Preferably, the specific method of the alkaline alcoholysis method includes: adding the raw material to be tested, alcohol and catalyst into a three-necked flask in proportion, placing the three-necked flask in an oil bath heating device, installing a condensing reflux device, starting stirring, and the stirring rate is 500-1500rpm; cooling to 150°C after the reaction is completed and stopping stirring, replacing the mechanical stirring reflux device with a distillation device, reducing the pressure with a water pump, heating to evaporate the alcohol, and stopping heating after distilling until no distilled components are produced; during the reaction, when the system is heated to 130°C, bubbles can be seen to be generated, and the flask gradually becomes a white thick slurry.
[0035] Preferably, the mass ratio of the raw material to be tested, the alcohol and the catalyst is 1:5-8:0.5-0.8.
[0036] Preferably, in step S11, the preparation method of the analyte includes: after the cleavage reaction is completed, hot water is added to the reaction container, stirring to completely dissolve the solid in the reaction container, filtering to remove insoluble matter, transferring the filtered solution to a beaker, and performing acid-base titration with dilute sulfuric acid to pH = 1.5 to 2.0 while stirring, and terminating the titration reaction; after multiple filtration and washing, placing it in an oven to dry, the analyte can be obtained.
[0037] Preferably, the temperature of the hot water is 85-95°C, preferably 90°C.
[0038] Preferably, the concentration of the dilute sulfuric acid is 0.4-0.6 mol / L.
[0039] Preferably, in step S12, the specific method of preparing the test object prepared in step S1 into a sample includes: adding ammonia water to the test object prepared in step S11, ultrasonically dissolving it, filtering it after dissolution to remove insoluble matter, and placing the filtrate in a sample bottle to prepare the sample.
[0040] Preferably, in step S12, when a high-efficiency capillary column is used to analyze the sample, the corresponding peak position of the chromatogram is that the peak position of the organic impurity p-toluic acid peak on the chromatogram is between 6.5 and 7.0 min.
[0041] Preferably, the inner diameter of the capillary is 60 μm to 80 μm, and the effective length is 50 cm to 70 cm.
[0042] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0043] The polyester fiber designed by the present invention has high quality and low coefficient of variation, is beneficial to increasing the elongation of primary fibers, and reducing phenomena such as fuzzy fibers, broken fibers, and floating fibers during the spinning process. DETAILED DESCRIPTION
[0044] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example 1
[0046] This embodiment discloses a high-quality, low-variance-coefficient polyester high-strength fiber, which is a polyester fiber obtained by processing polyester chips through alkaline alcoholysis or alkaline hydrolysis, wherein the content of p-toluic acid in the polyester chips after alkaline alcoholysis or alkaline hydrolysis is 40 to 100 ppm; the processing method includes a melt spinning process.
[0047] Preferably, the melt spinning process includes drying, melt extrusion, melt distribution, component spinning, filament cooling, oiling, drawing and heat setting, and winding of polyester chips having a p-toluic acid content of 40 to 100 ppm obtained by titration test after alkaline alcoholysis or alkaline hydrolysis.
[0048] Preferably, the specific method of the melt spinning process includes the following steps:
[0049] (1) Drying of polyester chips: After drying, the moisture content of polyester chips is controlled to ≤25ppm;
[0050] (2) Melt extrusion, melt distribution, and component spinning: polyester chips with a controlled moisture content of ≤25 ppm are fed into a screw extruder, melted at high temperature, and extruded and fed into component spinning via melt distribution;
[0051] (3) Cooling, oiling, drawing and heat setting of the filaments: The filaments are cooled, oiled and then drawn by hot rollers;
[0052] (4) Winding: The filament bundle is formed into a silk cake through a winding machine, and the winding speed is 2300-6700m / min.
[0053] Preferably, step (1) can be replaced by using polyester low-viscosity chips to continuously increase viscosity and then storing them in a nitrogen or dry air environment with a moisture content of ≤25 ppm.
[0054] Preferably, in step (2), the temperature of each zone in the screw extruder is 276-330° C., the head pressure is 10-17 MPa, the cooling air temperature of the filament bundle is 16-70° C., and the spinneret stretching ratio during the component spinning process is 200-1900.
[0055] Preferably, the oil content of the oil applied in step (3) is between 0.2% and 1.0%, the speed of one roller during hot roller stretching is between 385 and 3650 m / min, the maximum hot roller speed is between 2350 and 6750 m / min, the hot roller temperature during hot stretching is between 45 and 155° C., the hot roller heat setting temperature is between 200 and 260° C.; the total extension ratio is between 1.55 and 6.5; and the retraction speed difference is between 15 and 360 m.
[0056] Preferably, the linear density deviation rate of the polyester fiber is ±2.0%; the strength is ≥6.8 cN / dtex; the coefficient of variation at the breaking elongation is ≤29% is only less than 70% of the upper limit required for superior products in the Chinese national standard GB / T 16604-2017 polyester industrial filament.
[0057] Preferably, the intrinsic viscosity of the polyester fiber is ≥ 0.72 g / dl; more preferably, the intrinsic viscosity of the polyester fiber is ≥ 0.75 g / dl.
[0058] Example 2
[0059] The method for detecting the content of p-toluic acid in the polyester raw material in this embodiment comprises the following steps:
[0060] S11, cracking the raw material to be tested, decomposing the raw material to be tested into small molecules and producing trace impurities, extracting the small molecules and trace impurities, filtering, washing, and drying to obtain the object to be tested;
[0061] S12, preparing a sample from the test object prepared in step S11, analyzing the sample using a high-efficiency capillary chromatographic column, and testing the impurity content after polyester cracking.
[0062] Furthermore, the small molecule includes PTA (terephthalic acid).
[0063] Furthermore, the cleavage in step S11 is carried out by alkaline alcoholysis or alkaline hydrolysis, the cleavage temperature is 120 to 220° C., and the reaction time is 2 to 7 hours.
[0064] Furthermore, the cracking in step S11 adopts alkaline alcoholysis method, the alcohol used in the alkaline alcoholysis method is methanol or ethylene glycol, and the mass ratio of the raw material to be tested to the alcohol is 1:3-7.
[0065] Furthermore, the cleavage in step S11 is performed by alkaline hydrolysis, and the water used in the alkaline hydrolysis is deionized water; the mass ratio of the raw material to be tested to water is 1:3-7.
[0066] Furthermore, in step S11, the cracking reaction process also includes adding a catalyst, the catalyst includes sodium carbonate, and the mass ratio of the catalyst to the raw material to be tested is 0.5 to 1:1.
[0067] Furthermore, the specific method of the alkaline alcoholysis method includes: adding the raw material to be tested, alcohol and catalyst into a three-necked flask in proportion, placing the three-necked flask in an oil bath heating device, installing a condensing reflux device at the same time, starting stirring, and the stirring rate is 500-1500rpm; cooling to 150°C after the reaction is completed and stopping stirring, replacing the mechanical stirring reflux device with a distillation device, reducing the pressure with a water pump, heating to evaporate the alcohol, and stopping heating after distilling until there is no distilled component; during the reaction, when the system is heated to 130°C, bubbles can be seen to be generated, and the flask gradually becomes a white thick slurry.
[0068] Furthermore, the mass ratio of the raw material to be tested, the alcohol and the catalyst is 1:5-8:0.5-0.8.
[0069] Furthermore, in step S11, the preparation method of the analyte includes: after the cleavage reaction is completed, hot water is added to the reaction container, stirring to completely dissolve the solid in the reaction container, filtering to remove insoluble matter, transferring the filtered solution to a beaker, and performing acid-base titration with dilute sulfuric acid to pH = 1.5 to 2.0 while stirring, and terminating the titration reaction; after multiple filtration and washing, placing it in an oven to dry, the analyte can be obtained.
[0070] Furthermore, the temperature of the hot water is 85-95°C, preferably 90°C.
[0071] Furthermore, the concentration of the dilute sulfuric acid is 0.4-0.6 mol / L.
[0072] Furthermore, in step S12, the specific method of preparing the test object prepared in step S1 into a sample includes: adding ammonia water to the test object prepared in step S11, ultrasonically dissolving it, filtering it after dissolution to remove insoluble matter, and placing the filtrate in a sample bottle to prepare the sample.
[0073] Furthermore, in step S12, when a high-efficiency capillary column is used to analyze the sample, the corresponding peak position of the chromatogram is that the peak position of the organic impurity p-toluic acid peak on the chromatogram is between 6.5 and 7.0 min.
[0074] Furthermore, the inner diameter of the capillary is 60 μm to 80 μm, and the effective length is 50 cm to 70 cm.
[0075] The difference between virgin polyester and chemically recycled polyester is that chemically recycled polyester undergoes a high-temperature cracking and refining process, and will produce small molecules and impurities after depolymerization. The impurities include p-toluic acid, p-carboxybenzaldehyde (4CBA), and butyl acrylate (BA); p-toluic acid acts as an inhibitor in the reaction, which will cause the molecular chain to lose activity and the chain end to be closed, thereby stopping the growth of molecular weight. Its presence directly affects the crystallization properties, molecular weight and distribution of polyester, thereby having an important impact on the intrinsic quality, spinnability and quality of polyester; by selecting at least 20 chemically recycled polyesters and at least 20 The original polyester was used as a sample, and the samples were subjected to high-temperature pyrolysis, sample extraction, and high-efficiency capillary column analysis to obtain the p-toluic acid content, 4CBA content, and BA content. The p-toluic acid content, 4CBA content, and BA content were used as sample data, and the sample labels were input into the linear model for training. The training results showed that when the p-To1 content was less than 130ppm, the raw material to be tested was chemically recycled polyester, and when the p-toluic acid content was greater than 130ppm and less than 180ppm, the raw material to be tested was original polyester; and 4CBA and BA did not have comparison rules. This is because p-toluic acid is easily soluble in hot water, and some of the impurities will be washed away under hot water; the p-toluic acid content of the chemically recycled polyester material after repolymerization will be reduced compared with the original polyester.
[0076] Example 3
[0077] This embodiment is implemented on the basis of the above-mentioned embodiments 1-2, and the similarities with the above-mentioned embodiments are not repeated here.
[0078] In this embodiment, the polyester chips are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, which are used for tire cord fabrics. The polyester chips selected in this embodiment are titrated and tested for p-toluic acid content of 43ppm after alkaline alcoholysis or alkaline hydrolysis.
[0079] The processing method comprises the melt spinning process described in Example 1, wherein in step (2), the temperature of each zone in the screw extruder is 285-310° C., the head pressure is 13-16 MPa, and the cooling air temperature of the filament bundle is 17-65° C.;
[0080] In step (3), the maximum hot roller speed is 6100 m / min, the hot roller heat setting temperature is 230° C.; the total extension ratio is 1.88; and the retraction speed difference is 120 m.
[0081] Example 4
[0082] This embodiment is implemented on the basis of the above embodiment 3, and the similarities with the above embodiment are not repeated here.
[0083] In this embodiment, the polyester chips are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, which are used for tire cord fabrics. The polyester chips selected in this embodiment are titrated to test the p-toluic acid content of 69ppm after alkaline alcoholysis or alkaline hydrolysis.
[0084] In step (3), the maximum hot roller speed is 5750 m / min, the hot roller heat setting temperature is 242° C.; the total extension ratio is 2.05; and the retraction speed difference is 110 m.
[0085] Example 5
[0086] This embodiment is implemented on the basis of the above embodiment 3, and the similarities with the above embodiment are not repeated here.
[0087] In this embodiment, the polyester chips are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, and the 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers are used for tire cord fabrics. The polyester chips selected in this embodiment are subjected to alkaline alcoholysis or alkaline hydrolysis, and the content of p-toluic acid obtained by titration test of the polyester chips is 92ppm.
[0088] In step (3), the maximum hot roller speed is 5810 m / min, the hot roller heat setting temperature is 234° C.; the total extension ratio is 1.93; and the retraction speed difference is 100 m.
[0089] Example 6
[0090] This embodiment is implemented on the basis of the above embodiment 1, and the similarities with the above embodiment are not repeated here.
[0091] In this embodiment, the polyester chips are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, which are used for airbag fabrics and automobile seat belts. The polyester chips selected in this embodiment are titrated and tested for p-toluic acid content of 46ppm after alkaline alcoholysis or alkaline hydrolysis.
[0092] The processing method comprises the melt spinning process described in Example 1, wherein in step (2), the temperature of each zone in the screw extruder is 285-310° C., the head pressure is 13-16 MPa, and the cooling air temperature of the filament bundle is 17-65° C.;
[0093] In step (3), the maximum hot roller speed is 3220 m / min, the hot roller heat setting temperature is 254° C.; the total extension ratio is 5.4; and the retraction speed difference is 100 m.
[0094] Example 7
[0095] This embodiment is implemented on the basis of the above-mentioned embodiment 6, and the similarities with the above-mentioned embodiment are not repeated here.
[0096] In this embodiment, the polyester chips are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, which are used for airbag fabrics and automobile seat belts. The polyester chips selected in this embodiment are subjected to alkaline alcoholysis or alkaline hydrolysis, and the content of p-toluic acid obtained by titration test of the polyester chips is 71ppm.
[0097] In step (3), the maximum hot roller speed is 3150 m / min, the hot roller heat setting temperature is 251° C., the total extension ratio is 6.2, and the retraction speed difference is 130 m.
[0098] Example 8
[0099] This embodiment is implemented on the basis of the above-mentioned embodiment 6, and the similarities with the above-mentioned embodiment are not repeated here.
[0100] In this embodiment, the polyester chips are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, which are used for airbag fabrics and automobile seat belts. The polyester chips selected in this embodiment are subjected to alkaline alcoholysis or alkaline hydrolysis, and the p-toluic acid content obtained by titration test of the polyester chips is 90ppm.
[0101] In step (3), the maximum hot roller speed is 3410 m / min, the hot roller heat setting temperature is 247° C.; the total extension ratio is 5.7; and the retraction speed difference is 140 m.
[0102] Example 9
[0103] This embodiment is implemented on the basis of the above embodiment 1, and the similarities with the above embodiment are not repeated here.
[0104] In this embodiment, the polyester chips are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, which are used for conveyor belts, tarpaulins, air spring fabrics, industrial slings, and tent fabrics. The polyester chips selected in this embodiment are subjected to alkaline alcoholysis or alkaline hydrolysis, and the p-toluic acid content obtained by titration test of the polyester chips is 45ppm.
[0105] The processing method comprises the melt spinning process described in Example 1, wherein in step (2), the temperature of each zone in the screw extruder is 285-310° C., the head pressure is 13-16 MPa, and the cooling air temperature of the filament bundle is 17-65° C.;
[0106] In step (3), the maximum hot roller speed is 3450 m / min, the hot roller heat setting temperature is 224° C., the total extension ratio is 5.2, and the retraction speed difference is 100 m.
[0107] Example 10
[0108] This embodiment is implemented on the basis of the above-mentioned embodiment 9, and the similarities with the above-mentioned embodiment are not repeated here.
[0109] In this embodiment, the polyester chips are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, which are used for conveyor belts, tarpaulins, air spring fabrics, industrial slings, and tent fabrics. The polyester chips selected in this embodiment are subjected to alkaline alcoholysis or alkaline hydrolysis, and the p-toluic acid content obtained by titration test of the polyester chips is 65ppm.
[0110] In step (3), the maximum hot roller speed is 3370 m / min, the hot roller heat setting temperature is 225° C., the total extension ratio is 5.3, and the retraction speed difference is 100 m.
[0111] Embodiment 11
[0112] This embodiment is implemented on the basis of the above-mentioned embodiment 9, and the similarities with the above-mentioned embodiment are not repeated here.
[0113] The polyester chips in this embodiment are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, which are used for conveyor belts, tarpaulins, air spring fabrics, industrial slings, and tent fabrics. The polyester chips selected in this embodiment are titrated and tested for p-toluic acid content of 87ppm after alkaline alcoholysis or alkaline hydrolysis.
[0114] In step (3), the maximum hot roller speed is 3380 m / min, the hot roller heat setting temperature is 234° C.; the total extension ratio is 5.5; and the retraction speed difference is 180 m.
[0115] Comparative Example 1
[0116] In this embodiment, the polyester chips are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, which are used for tire cord fabrics. The polyester chips selected in this embodiment are titrated and tested for p-toluic acid content of 31ppm after alkaline alcoholysis or alkaline hydrolysis.
[0117] In step (3), the maximum hot roller speed is 5890 m / min, the hot roller heat setting temperature is 247° C.; the total extension ratio is 1.89; the retraction speed difference is 190 m, and other conditions are the same as those in Example 3.
[0118] Comparative Example 2
[0119] In this embodiment, the polyester chips are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, and the 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers are used for tire cord fabrics. The polyester chips selected in this embodiment are titrated and tested for p-toluic acid content of 157ppm after alkaline alcoholysis or alkaline hydrolysis.
[0120] In step (3), the maximum hot roller speed is 5760 m / min, the hot roller heat setting temperature is 235° C.; the total extension ratio is 2.03; the retraction speed difference is 230 m, and other conditions are the same as those in Example 3.
[0121] Comparative Example 3
[0122] In this embodiment, the polyester chips are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, which are used for airbag fabrics and automobile seat belts. The polyester chips selected in this embodiment are subjected to alkaline alcoholysis or alkaline hydrolysis, and the content of p-toluic acid obtained by titration test of the polyester chips is 27ppm.
[0123] In step (3), the maximum hot roller speed is 3200 m / min, the hot roller heat setting temperature is 241° C.; the total extension ratio is 6.0; the retraction speed difference is 110 m, and other conditions are the same as those in Example 6.
[0124] Comparative Example 4
[0125] In this embodiment, the polyester chips are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, which are used for airbag fabrics and automobile seat belts. The polyester chips selected in this embodiment are titrated and tested for p-toluic acid content of 145ppm after alkaline alcoholysis or alkaline hydrolysis.
[0126] In step (3), the maximum hot roller speed is 3560 m / min, the hot roller heat setting temperature is 230° C.; the total extension ratio is 5.8; the retraction speed difference is 120 m, and other conditions are the same as those in Example 6.
[0127] Comparative Example 5
[0128] The polyester chips in this embodiment are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, which are used for conveyor belts, tarpaulins, air spring fabrics, industrial slings, and tent fabrics. The polyester chips selected in this embodiment are subjected to alkaline alcoholysis or alkaline hydrolysis, and the p-toluic acid content obtained by titration test of the polyester chips is 33ppm.
[0129] In step (3), the maximum hot roller speed is 3420 m / min, the hot roller heat setting temperature is 230° C.; the total extension ratio is 5.5; the retraction speed difference is 140 m, and other conditions are the same as those in Example 9.
[0130] Comparative Example 5
[0131] The polyester chips in this embodiment are processed to produce 1000d high-quality, low-variation coefficient high-modulus, low-shrinkage polyester fibers, which are used for conveyor belts, tarpaulins, air spring fabrics, industrial slings, and tent fabrics. The polyester chips selected in this embodiment are titrated and tested for p-toluic acid content of 146ppm after alkaline alcoholysis or alkaline hydrolysis.
[0132] In step (3), the maximum hot roller speed is 3270 m / min, the hot roller heat setting temperature is 241° C.; the total extension ratio is 5.2; the retraction speed difference is 130 m, and other conditions are the same as those in Example 9.
[0133] The polyester fibers prepared in the above-mentioned embodiments 3-5 and comparative examples 1-2 are used in tire cord fabrics. The performance tests of the above-mentioned embodiments 3-5 and comparative examples 1-2 are respectively carried out. The preparation conditions and the obtained results are shown in Table 1 below.
[0134] Table 1
[0135]
[0136]
[0137] It can be clearly seen from Table 1 that the raw material PT acid test results of the polyester fibers prepared in Comparative Examples 1 and 2 are beyond the preparation range required by the present application when applied to tire cord fabrics. From the test results, the linear density deviation rate, breaking strength variation coefficient, breaking elongation variation coefficient, broken fiber rate and hairiness number of Comparative Examples 1-2 are significantly higher than those of Examples 3-5, and the performance is poor; while Examples 3-5 have high quality and low variation coefficient, which is beneficial to increase the elongation of primary fibers and reduce the phenomena of hairiness, broken fibers and floating fibers during the spinning process.
[0138] The above-mentioned Examples 6-8 and Comparative Examples 3-4 are all applications of the prepared polyester fibers in airbag fabrics and automobile seat belts. The above-mentioned Examples 6-8 and Comparative Examples 3-4 are respectively subjected to performance tests, and the preparation conditions and the obtained results are shown in Table 2 below.
[0139] Table 2
[0140]
[0141] It can be clearly seen from Table 2 that the raw material PT acid test results of the polyester fibers prepared in Comparative Examples 3 and 4 are beyond the preparation range required by the present application when applied to airbag fabrics and automobile seat belts. From the test results, the linear density deviation rate, breaking strength variation coefficient, breaking elongation variation coefficient, broken fiber rate and hairiness number of Comparative Examples 3-4 are significantly higher than those of Examples 6-8, and the performance is poor; while Examples 6-8 have high quality and low variation coefficient, which is beneficial to increase the elongation of primary fibers and reduce the phenomena of hairiness, broken fibers and floating fibers during the spinning process.
[0142] The above-mentioned Examples 9-11 and Comparative Examples 5-6 are all applications of the prepared polyester fibers in conveyor belts, tarpaulins, air spring fabrics, industrial slings, and tent fabrics. The above-mentioned Examples 9-11 and Comparative Examples 5-6 were respectively subjected to performance tests, and the required preparation conditions and the obtained results are shown in Table 3 below.
[0143] Table 3
[0144]
[0145] It can be clearly seen from Table 3 that the raw material PT acid test results of the polyester fibers prepared in Comparative Examples 5 and 6 are beyond the preparation range required by the present application when applied to conveyor belts, tarpaulins, air spring cloths, industrial slings, and tent cloths. From the test results, the linear density deviation rate, breaking strength variation coefficient, breaking elongation variation coefficient, broken fiber rate, and hairiness number of Comparative Examples 5-6 are significantly higher than those of Examples 9-11, and the performance is poor; while Examples 9-11 have high quality and low variation coefficient, which is beneficial to increase the elongation of primary fibers and reduce the phenomena of hairiness, broken fibers, floating fibers, etc. during the spinning process.
[0146] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A high-quality, low-variance polyester high-strength fiber, characterized in that: The polyester fiber is obtained by processing polyester chips through alkaline alcoholysis or alkaline hydrolysis, wherein the content of p-toluic acid in the polyester chips after alkaline alcoholysis or alkaline hydrolysis is 40-100 ppm; the processing method includes a melt spinning process.
2. A polyester high-strength fiber with high quality and low coefficient of variation according to claim 1, characterized in that: The melt spinning process includes drying, melt extrusion, melt distribution, component spinning, filament cooling, oiling, drawing, heat setting and winding of polyester chips with a p-toluic acid content of 40 to 100 ppm obtained by titration test after alkaline alcoholysis or alkaline hydrolysis.
3. A polyester high-strength fiber with high quality and low coefficient of variation according to claim 2, characterized in that: The specific method of the melt spinning process comprises the following steps: (1) Drying of polyester chips: After drying, the moisture content of polyester chips is controlled to ≤25ppm; (2) Melt extrusion, melt distribution, and component spinning: polyester chips with a controlled moisture content of ≤25 ppm are fed into a screw extruder, melted at high temperature, and extruded and fed into component spinning via melt distribution; (3) Cooling, oiling, drawing and heat setting of the filaments: The filaments are cooled, oiled and then drawn by hot rollers; (4) Winding: The filament bundle is formed into a silk cake through a winding machine, and the winding speed is 2300-6700m / min.
4. A polyester high-strength fiber with high quality and low coefficient of variation according to claim 3, characterized in that: In step (2), the temperature of each zone in the screw extruder is 276-330° C., the head pressure is 10-17 MPa, the cooling air temperature of the filament bundle is 16-70° C., and the spinneret stretching ratio during the component spinning process is 200-1900.
5. The high-quality, low-variance-coefficient polyester high-strength fiber according to claim 3, characterized in that: The oil content of the oil applied in step (3) is 0.2% to 1.0%, the speed of one roller during hot roller stretching is 385 to 3650 m / min, the maximum hot roller speed is 2350 to 6750 m / min, the hot roller temperature during hot stretching is 45 to 155° C., the hot roller heat setting temperature is 200 to 260° C.; the total extension ratio is 1.55 to 6.5; and the retraction speed difference is 15 to 360 m.
6. The high-quality, low-variance-coefficient polyester high-strength fiber according to claim 1, characterized in that: The linear density deviation rate of the polyester fiber is ±2.0%; the strength is ≥6.8cN / dt ex; the coefficient of variation at breaking elongation ≤29% is only less than 70% of the upper limit required for superior products in China's national standard GB / T 16604-2017 polyester industrial filament.
7. The high-quality, low-variance polyester high-strength fiber according to claim 1, characterized in that: The intrinsic viscosity of polyester fiber is ≥0.72g / dl.
8. Application of a high-quality, low-variance polyester high-strength fiber, characterized in that: The high-quality, low-variance-coefficient polyester high-strength fiber described in any one of claims 1 to 7 is applied to tire cord fabrics, airbag fabrics, car seat belts, conveyor belts, tarpaulins, air spring fabrics, industrial slings, tent fabrics, sewing threads, and dipped cords.
9. The use of a high-quality, low-variance polyester high-strength fiber according to claim 8, characterized in that: When polyester high-strength fiber is used in tire cord fabric, its linear density deviation rate is ±1.3%; breaking strength ≥7.00cN / dt ex, breaking strength variation coefficient ≤1.9%, breaking elongation variation coefficient ≤5.5%; The spinning process is as follows: the raw materials are input into a screw extruder for high-temperature melting and extrusion into a spinning assembly, the temperature of each zone of the screw is 282-330°C, the head pressure is 11-17 MPa, the temperature of the cooling zone is 17-68°C, the speed of one roller is 2200-3500 m / min, the maximum hot roller speed is 4700-6500 m / min, the heat setting temperature is 210-250°C; the total extension ratio is 1.7-2.5; and the retraction is 60-280 m.
10. The use of a high-quality, low-variance polyester high-strength fiber according to claim 8, characterized in that: When polyester high-strength fiber is used in industrial slings and automobile seat belts, its linear density deviation rate is ±1.3%; breaking strength ≥8.2cN / dt ex, breaking strength variation coefficient ≤1.9%, breaking elongation variation coefficient ≤5.5%; The spinning process is as follows: the raw materials are input into a screw extruder for high-temperature melting and extrusion into a spinning assembly, the temperature of each zone of the screw is 280-315°C, the head pressure is 10-16MPa, the temperature of the cooling zone is 17-27°C, the speed of one roller is 400-1000m / min, the maximum hot roller speed is 2600-4000m / min, the heat setting temperature is 200-258°C; the total extension ratio is 5.4-6.2; and the retraction is 50-280m.
11. The use of a high-quality, low-variance polyester high-strength fiber according to claim 8, characterized in that: When polyester high-strength fiber is used in airbag fabrics, conveyor belts, tarpaulins, air spring fabrics, and tent fabrics, its linear density deviation rate is ±1.3%; breaking strength is ≥6.8cN / dt ex, breaking strength variation coefficient is ≤1.9%, and breaking elongation variation coefficient is ≤5.5%; The spinning process is as follows: the raw materials are input into a screw extruder for high-temperature melting and extrusion into a spinning assembly, the temperature of each zone of the screw is 280-315°C, the head pressure is 12-16MPa, the temperature of the cooling zone is 16-25°C, the speed of one roller is 400-1000m / min, the maximum hot roller speed is 2500-3900m / min, the heat setting temperature is 210-260°C; the total extension ratio is 5.1-6.3; the retraction is 80-330m.